Effectiveness of ultrasound-guided hydrostatic reduction of intussusception in children - Datta, Sumi; Md Jamal, -; Rahman, Yesmina; Hussain, Mahbuba; Yeshmina, Fahmida; Rabbi, Akanda Fazle; Sarker, Pratul Kumar (Journal of Dhaka Medical College, 2020)
Aim: To review the effectiveness of ultrasound- guided hydrostatic reduction of intussusception in children. Methods: This prospective interventional study was done during one year period from January 2014 to December 2014 in the department of Radiology and Imaging of Dhaka Medical College and Hospital, Dhaka and included 30 children clinically and radiologically diagnosed as intussusception with symptoms d” 48 hours. They underwent ultrasound-guided hydrostatic reduction using normal saline and the effectiveness of this technique was reviewed. Results: Majority of the study population were in the age group of 7-24 months with mean age of 9.04± 2.48 months. 100% patients who presented within 24 hours of their symptoms achieved successful reduction whereas success rate of reduction were 95% and 0% respectively in patients presented within 24-36 hours and after 36 hours of their symptoms. 60% cases required 5-10 minutes for successful reduction, 20% cases required 3-5 minutes and 10% patients needed > 10 minutes. Within 3 attempts, reduction happened in 90% cases whereas 10% cases failed to reduce. No case was tried for reduction after 3 attempts in consideration of the bowel pathology and complications. Only 10% patients developed negligible complications. No case showed recurrence. Conclusion: Ultrasound guided hydrostatic reduction of intussusception is an effective nonoperative treatment of intussusception in children because of its high success rate, less complications and recurrence rate. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 134-140